IN VITRO CULTIVATION OF RARE AND ENDEMIC ALLIUM SP. SPECIES - Novakovskaya А.P.; Raizer , O.B.; Danilova А.N.; Khapilina О.N. (Eurasian Journal of Applied Biotechnology, 2022)
Here present the results of studies on the in vitro cultivation of rare, dangerous and endemic species of Allium genus (A. ledebourianum, A. altaicum, A. schoenoprasum, A. obliquum) grown in the territory of the Kazakh Altai. The seeds of onions collected in the locations of their natural growth, namely the territory of the Kazakh Altai, were used as material to conduct the study. The sterilization protocols for seeds of various Allium species were established. It was found that it is necessary to apply the procedure based on multiple-step disinfection and various sterilizing agents to obtain aseptic shoots of different Allium species. The seed germinating efficiency of rare and endemic species of Allium sp. in vitro conditions were analyzed during the study.